Being and becoming: a revealing glimpse of L2 writer identity through metaphors - Kittika Limpariwatthana; Bee Chamcharatsri (Cogent Education)
English language teaching has been introduced in Thailand since 1921. As English is a foreign language in Thailand, its primary functions in society have been linked to tourism, economic growth, and enhancing socioeconomic status. Currently, English is a mandatory subject for Thai students from K-12. However, English writing has not been a central focus in the basic curriculum. At the university level, writing courses aim to help students compose English essays across disciplines. Despite its importance, research on writing instruction in Thailand remains limited, and studies on the identity construction of second language (L2) writers are even scarcer. This study addresses deeper insights into how Thai undergraduate students construct their writer identities in English writing classrooms. Using an arts-based qualitative approach, we analyzed how four Thai undergraduate students constructed their L2 writer identities through visual metaphors of their learning experiences. Grounded in social constructionism, we argue that metaphor enables students to express their lived experiences—writing for the self and becoming a resilient writer—as they develop writing skills. This study underscores the arts-based research in capturing the complexity of writer identity. Pedagogically, we advocate for incorporating multimodal approaches to address the diverse experiences of Thai EFL students.